The Definitive Hand Book of Business Continuity Management - Hiles, Andrew (New York: Wiley, 2001)
Hiles and Barnes provide comprehensive conceptual and practical guidance for managers and businesses who want to establish a strategy for protecting their organization from disruption and disaster.
Includes Bibliographical References and Index
Keywords: Business planning; Crisis management; Emergency management